The concept and features of trade relations as a subject of Trade Law (Bulletin of Kharkiv National University of Internal Affairs, 2023)
It is established that Trade Law is a branch of law which regulates legal relations arising in the course of business activities, in particular, those related to the purchase and sale of goods and services, as well as other transactions related to the relevant processes. This branch of law contains legal rules that govern the establishment, registration, management and liquidation of enterprises, transactions, fair competition, consumer protection, intellectual property, patents and trademarks, and other aspects of business activities related to trading.The article proves that trade legal relations as the subject matter of the Trade Law branch are a complex set of property and non-property relations arising between trade law entities in relation to the sale and purchase of goods and services. These legal relations include all stages of the process of buying and selling goods and services: from finding partners and signing a contract to making payments and fulfilling the parties’ obligations.It is argued that the key features of trade legal relations are as follows: parties to trade legal relations are not only legal entities, but also individuals; one of the parties to legal relations is necessarily an entity which sells goods and services; the relevant relations arise not only by concluding a written agreement, they may also be oral; these legal relations are governed by the rules of not only Trade Law, but also other branches of law which are closely intertwined with each other; parties to trade relations usually have a single goal which is a commercial one; the quality and efficiency of trade relations affect the development of the state's economy as a whole, as well as the financial and economic condition of each individual; regulation of trade relations is an important guarantee of observance of the rights and freedoms of a person using services, works, etc.